Biaya Modal Perusahaan di Indonesia: Tanggung Jawab Sosial dan Tata Kelola Perusahaan - Pramuji H. Jadi, Amrie Firmansyah,Arifah F. Andriyani, M. Luthfi Mahrus, Wahyudi Febrian, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The high capital cost indicates the company's risk to obtain funding from debt and equity. The test in this study aims to prove the association between corporate social responsibility and corporate governance with the cost of capital. This study employs data sourced from financial reports and annual reports of the listed companies on the Indonesia Stock Exchange, downloaded from www.idx.co.id. In addition, this research data also employs stock price information sourced from finance.yahoo.com. The sample selection in this study used purposive sampling with a total sample of 260 observations from 65 companies from 2016 to 2019. The hypothesis test in this study used multiple linear regression analysis for panel data. This study concludes that corporate governance is positively associated with the cost of capital, while corporate social responsibility is negatively associated with the cost of capital. This study suggests that Indonesia's capital market supervisory authority needs to improve its governance policies and governance oversight mechanisms for companies listed on the Indonesia Stock Exchange.